Software Transparency and Purity. - Meunier, Pascal (Communications of the ACM, 2008)
The author presents information on computer software programs that contain functions that were designed to be hidden from software consumers. Early examples of this practice came in the form of Trojan horses and Easter eggs, but it has become more common. Software transparency is when all the functions of the software are disclosed. Transparency is necessary for proper risk management. Also discussed are secretive functions in TiVo's software, Warden software, and Microsoft Live OneCare.